When borders transnationalize people: reframing the migrant transnationalism in the Andean tri-border area - Guizardi,Menara (2018)
This article derives from ethnographic studies developed in the Northern Chilean territories that lie adjacent to Peru and Bolivia. The research results suggest that the daily activities of transborder inhabitants generate frictions between the local inscription of social practices, and the transnationalization of communitarian knowledge, economies and memories. These frictions situationally update the national identities in these areas. Over the last two decades, an idea has prevailed in migratory studies that the migrants border crossings articulate transnational social fields between origin and host societies, leading to a globalization from below. Ethnographic findings defy this conception, since the social networks and practices that interconnect these borderlands predate the establishment of the national frontiers. It was not the communities who transnationalized the territories: the borders transnationalized them. I will illustrate this assertion by ethnographically following Joanna, an Aymaran shepherdess that found a transnational solution to the lack of successors to her shepherding activities.